SISTEM AGRO-KONSERVASI LAHAN SAWIT DENGAN BIOSOILDAM UNTUK PENINGKATAN DAYA DUKUNG TANAH INSEPTISOL - Widiasmadi, Nugroho (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The objective of this analysis improvement of soil infiltration rate on Litosol agroland fo pady field with involve biofertilizer MA-11 on the Biosoildam. As a control is original soil without microbial activity triggered. The research was carried out on July to Agustus 2021 at area of shallot agroland in Blora Districts. The research was use double ring infiltrometer to measure soil infiltration with three replication on each distance from Biohole and use electrolit conductivity meter (EC) to measure soil fertility by salt ion consentration and soil acidity. The measurement was done in every five minute and observtian periode every fifteen days along forty five days. The result of research show that the highest of infiltration rate, infiltration capacity , fertility & acidity was happened on soil with involve Biofertilizer MA-11. The infiltration rate shows a constant value at a level of 237 to 327 cm / hour which is achieved after the 29 th day. Meanwhile, the EC value in stable conditions is achieved on the 29th day with a value between 935 -1385 uS / cm. So that the activity of biological agents on Andosol soil with the infiltration level will be optimal on day 32.